Touring the Indigenous or Transforming Consciousness? Reflections on Teaching Indigenous Tourism at University - Higgins-Desbiolles, Freya (The Australian Journal of Indigenous Education, 2007)
Abstract The role of the non-Indigenous educator and researcher in education on Indigenous issues is becoming the subject of critical scrutiny. Indigenous academics are successfully turning the gaze on non-Indigenous peers and practices. This paper narrates some of the experiences of a non-Indigenous educator teaching an undergraduate elective Indigenous tourism course. The educator has attempted to respect the principles of an evolving Indigenist paradigm in the development, running and review of the course. In particular, the educator consulted with Indigenous academics and leaders in the development of the course and its curriculum; privileged Indigenous voices throughout the curriculum (in readings, audio-visuals, guest lectures and tutorial exercises); and facilitated student interaction with the local Indigenous community and land. My work as a non-Indigenous educator in the new academic field of tourism studies is currently pivotally important because Indigenous academics are not yet asserting their claim to this field. In my attempts to adhere to an Indigenist paradigm I aim to create important opportunities to ensure appropriate discourse and encourage Indigenous academics into the field. In relation to appropriate discourse and learning, student feedback so far indicates important transformations in consciousness are occurring. However, the problematic of the non-Indigenous educator speaking for Indigenous peoples as “essentialised Others” remains a key concern. While the tensions between Indigenous and non-Indigenous in the conduct of Indigenous education are real and important, this work in the teaching of Indigenous tourism suggests that the resolution of tensions require alliances and shifts in power.